Legal Protection for Consumers Against Unilateral Changes to Concert Venues - Lutvia Aulia Azzahra; Dadan Taufik Fathurohman (Riviera Publishing, 2026)
The rapid growth of music concerts in Indonesia has increased legal concerns regarding consumer rights, particularly when promoters unilaterally change concert venues after tickets have been purchased. Such changes may cause material and immaterial losses because consumers often consider location, accessibility, facilities, and initial event information before making a purchase. This study aims to analyze the legal framework governing consumer protection against unilateral changes to concert venues and to examine the legal protection and remedies available to affected consumers. This research uses a normative juridical method with statutory and case approaches. The data consist of primary legal materials, including Law No. 8 of 1999 on Consumer Protection, the Civil Code, and Law No. 1 of 2023 on the Criminal Code, supported by secondary legal materials such as books, journals, previous studies, and relevant cases. The results show that unilateral venue changes may violate consumers' rights to accurate information, proper service, and compensation, as regulated in Articles 4, 7, 18, and 19 of the Consumer Protection Law. Such conduct may also constitute breach of contract under Article 1243 and violate good faith under Article 1338 of the Civil Code. In conclusion, consumers are entitled to preventive and repressive legal protection through refunds, compensation, BPSK or BPKN mediation, civil lawsuits, and criminal reports when fraud or embezzlement is indicated.